A new mouse model of impaired wound healing after irradiation. Issue 2 (April 2013) - Tsumano, Tomoko; Kawai, Kenichiro; Ishise, Hisako; Nishimoto, Soh; Fukuda, Kenji; Fujiwara, Toshihiro; Kakibuchi, Masao
Abstract Radiation has many benefits and is an important treatment for cancer therapy. However, it also has unfavourable side-effects. Among these side-effects, the impairment of wound healing in the skin is a major problem in clinics. Although many attempts have been made to overcome this shortcoming, there are few effective treatments for impaired wound healing after irradiation. One reason for this is that it is hard to obtain good animal models for researching this topic. In this study, two different models were created and investigated. In one model, rectangular flaps were created on the backs of mice and irradiated while the other parts of their bodies were covered with a lead board. In another model, the lower limbs were exposed to radiation. In each model, several doses of irradiation were tested. Skin ulcers were created in the irradiated area, and the wound healing process was observed. In order to verify the usefulness of the model, adipose derived stromal cells were injected into the wound and the healing rate was calculated. In the flap model, the flaps contracted and formed linear scars. On the other hand, in the thigh model, 15 Gy irradiation resulted in slow wound healing but no strong inflammation or necrosis. The transplantation of adipose tissue derived stromal cells into the irradiated thigh wound improved the wound healing. This study suggested that irradiation of the lower limb at ∼ 15 Gy might be an appropriate model for basic research into wound healing in irradiated skin.